Study the Usage behavior of Mobile network Services of Lao Telecommunications Public Company in Xayabouly Province - phetsavong, somesack (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research study examined the usage behavior of mobile network services provided by Lao Telecommunications Public Company in Xayabouly Province. The objectives of the study were to investigate the usage behavior of customers using mobile network services of Lao Telecommunications Public Company in Xayabouly Province, and to assess the level of customer satisfaction with the quality of these services. The research was conducted as a survey using questionnaires to collect data from customers currently using the mobile network services in Xayabouly Province. The data were analyzed using SPSS statistical software to calculate frequencies, percentages, means, and standard deviations. The results revealed that most customers learned about the services through the internet and made their own decisions when choosing to use them. A majority had been using their phone numbers for more than two years and chose the service primarily for its quality and reliable signal coverage. Most customers mainly used mobile internet (data), accessed the service more than five times per month, and used it primarily for work or business purposes. Additionally, most customers used prepaid mobile numbers, spent between 50,000 to 100,000 kip per month on services, and preferred to use network services between 08:01 and 12:00 hours. Customer satisfaction with the quality of mobile network services was found to be high. Key areas of satisfaction included equal service provision, timely service delivery, customer participation, adequate service availability, understanding and meeting customer expectations, follow-up with customers, advanced and modern services, continuous service delivery, relationship building with customers, and effective communication management.